New metal extractants and super-acidic ionic liquids derived from sulfamic acid. Issue 43 (10th May 2016) - Dupont, David; Renders, Evelien; Raiguel, Stijn; Binnemans, Koen
Abstract : N -Alkylated sulfamic acid derivatives are very interesting for metal processing. A new class of metal extractants and super-acidic ionic liquids is introduced. Abstract : Sulfamic acid (NH3 –SO3 ) is an acidic zwitterion with many applications. N -Alkylated derivatives are introduced, which can be used as a new class of metal extractants R2 NH–SO3 and as new super-acidic ionic liquids [R2 NH–SO3 H][Tf2 N]. The synthesis, properties and novel applications of this versatile platform are discussed.